Ecotourism: the 'human shield' for wildlife conservation in the Osa Peninsula, Costa Rica. Issue 3 (2nd July 2020) - Lopez Gutierrez, Beatriz; Almeyda Zambrano, A. M.; Mulder, G.; Ols, C.; Dirzo, R.; Almeyda Zambrano, S. L.; Quispe Gil, C. A.; Cruz Díaz, J.C.; Alvarez, D.; Valdelomar Leon, V.; Villareal, E.; Sanchez Espinosa, A.; et al.
ABSTRACT: The sustainability and efficiency of ecotourism regarding biodiversity conservation are under constant scrutiny and often dismissed based on negative effects arising from other types of nature-based tourism. Our study assess the impacts of infrastructure, human activity, and environmental factors on medium-large ground terrestrial species within the Lapa Rios Ecolodge Nature Reserve; results indicate that restoration, preservation, and conservation efforts are responsible for the wide range of species found within their reserve, including increased abundance of highly threatened rodents and ground birds. There is no indication that visitation or tour activities have negative impacts on wildlife; instead, the Ecolodge effectively created a 'human shield' that weakens threats to wildlife arising from hunting, logging, and gold mining. This shield effect ripples across the Osa Peninsula through the socio-economic benefits provided by ecotourism. Our results support a conservation model incorporating private reserves and parks to sustain biodiversity.